2019
DOI: 10.1186/s12943-019-1024-0
|View full text |Cite
|
Sign up to set email alerts
|

miR-301a promotes lung tumorigenesis by suppressing Runx3

Abstract: Background Our previous report demonstrated that genetic ablation of miR-301a reduces Kras -driven lung tumorigenesis in mice. However, the impact of miR-301a on host anti-tumor immunity remains unexplored. Here we assessed the underlying molecular mechanisms of miR-301a in the tumor microenvironment. Methods The differentially expressed genes were identified by using deep sequencing. The immune cell counts, and cytokines expression were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 40 publications
(54 reference statements)
3
38
0
Order By: Relevance
“…5 c, d). As RUNX3 is located in 1p36, a region often deleted in breast cancer [ 29 , 30 ], we focus this study on the regulatory role of this transcription factor. Additionally, the transcriptional levels of RCAN1.1 and RCAN1.2 were not changed when RUNX3 was knocked down (Additional file 3 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 c, d). As RUNX3 is located in 1p36, a region often deleted in breast cancer [ 29 , 30 ], we focus this study on the regulatory role of this transcription factor. Additionally, the transcriptional levels of RCAN1.1 and RCAN1.2 were not changed when RUNX3 was knocked down (Additional file 3 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…miR‐130b‐3p also plays a role in tumorigenesis and development, such as endometrial cancer 37 and non‐small cell lung cancer 18 . Research on miR‐301a‐3p and miR‐301b‐3p has focused on pancreatic, 38 colorectal, 39 hepatocellular, 16 and lung cancer 17 . These miRNAs are upregulated and play a pro‐cancer role in many cancers, and high expression in tumor tissues is often associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the miR‐130 family (miR‐130a‐3p, miR‐130b‐3p, miR‐301a‐3p, and miR‐301b‐3p) share common seed sequences, and they perform similar biological functions. They have been reported to promote cell proliferation and upregulation in several types of cancer 14‐20 . A recent study showed that the miR‐130 family may play a vital role in the occurrence and development of BC by regulating signal pathways through various target genes, including PTEN and PTPN11 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an increasing number of scientific researches have proposed that miRNAs could exert the biological roles through direct binding to the 3′UTR of their downstream target mRNAs [ 17 , 18 , 21 ]. In order to clarify the possible molecular mechanisms underlying the oncogenic effects of miR-183-5p in HCC, we carried out further mechanistic studies.…”
Section: Discussionmentioning
confidence: 99%